A chiral route to the synthesis of (2S, 3aR, 7aS)-tert-butyl hexahydro-2, 5-methanopyrrolo[3, 2-c]pyridine-1(4H)-carboxylate, an intermediate for nicotinic acetylcholine receptors agonists. (19th November 2022) - Jarugu, Lokesh Babu; Reddy, China Anki; Chikkananjaiah, Nanjundaswamy Kanikahalli; Li, Jianqing; Mathur, Arvind; Gupta, Anuradha
Abstract: A synthesis of ( 2S, 3aR, 7aS )- tert -butyl hexahydro-2, 5-methanopyrrolo[ 3, 2-c ]pyridine-1(4 H )-carboxylate (1A ), a key intermediate for tricyclic compounds found as potent α7 nicotinic acetylcholine receptor ligands, following a novel chiral route is described here. The new chiral route circumvented two major challenges in the earlier route by avoiding high catalyst loading of pyrophoric Pd/C and reduced reaction time for the hydrogenation. The current methodology starts with a chirally defined intermediate which gives a strategic advantage over the previous scheme by being more convergent. Some of these improvements are discussed in detail in the current work. Graphical abstract: Image 1